THE ROLE OF SPEAKING IN LANGUAGE LEARNING - Sabirova Nadira Maxmudovna (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
Interest in teaching languages to learners has been steadily growing in recent years. The capacity of speaking two or more languages is now the norm rather than the exception. For example, today English is offered in primary and even pre-school education in Uzbekistan. Thus, the concern on how to teach foreign languages has been at the centre of discussion in the world of education since the origins of teaching. Many theories about learning and teaching languages have been proposed from historical and contemporary perspectives so far, and many changes in language teaching methods have occurred, as well as changes in the kind of learners` needs.